2007
DOI: 10.18433/j3rp46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine on Pulmonary Inflammatory Responses and Survival in Rats Exposed to Polymicrobial Sepsis

Abstract: -PURPOSE.Ketamine is reported to suppress production of proinflammatory cytokines and activity of nuclear factor-kappa B (NF-κB) after lipopolysaccharide (LPS) stimulation. Our study was designed to investigate the effects of ketamine on pulmonary inflammatory responses and survival in a clinically relevant model of polymicrobial sepsis, induced by cecal ligation and puncture (CLP). METHODS. After the induction of sepsis or sham-operation, animals were treated with ketamine (0.5, 5 or 10 mg/kg) or saline (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
21
2
Order By: Relevance
“…On the other hand, ketamine's role in neuroanesthesia is limited because of its association with increased intracranial pressure and other side effects such as psychotropic properties, tachycardia and hypertension [26]. Recent years studies have shown that ketamine plays a protective role against lung injury, via its anti-inflammatory properties [8][9][10]. Under ketamine anesthesia, neurogenic pulmonary edema is less pronounced in a rat model of spinal cord injury, and the mortality of severely burnt rats is reduced [28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, ketamine's role in neuroanesthesia is limited because of its association with increased intracranial pressure and other side effects such as psychotropic properties, tachycardia and hypertension [26]. Recent years studies have shown that ketamine plays a protective role against lung injury, via its anti-inflammatory properties [8][9][10]. Under ketamine anesthesia, neurogenic pulmonary edema is less pronounced in a rat model of spinal cord injury, and the mortality of severely burnt rats is reduced [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine has been shown to attenuate symptoms of endotoxemia in a lipopolysaccharide-induced rat model of sepsis, by reducing nuclear factor kappa B (NF-kappa B) activity and tumor necrosis factor-alpha (TNF-α) production [29], and decreasing the expression of iNOS in various rat tissues [30]. Furthermore, Yu et al found that ketamine at sub-anesthetic doses also suppress the production of inflammatory cytokines on lung tissue such as TNF-α and interleukin-6 (IL-6), attenuate NF-kappa B activity, and inhibit toll-like receptor 2 (TLR2) and TLR4 expression in polymicrobial sepsis [8]. In addition, ketamine has weak suppressive effect on reactive oxygen species (ROS) production by neutrophils and modulate the stimulated adhesion molecule expression [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations